Żądanie Antygony. Nienormatywny model rodziny Judith Butler - Lubowicka, Grażyna (EDUsfera. Ewa Jurczyk-Romanowska, 2019)
The problem of a decomposed and diverse family in postmodernity or a family subjected to deformations and displacements, and the question about which model(s) it may be heading, is presented by Judith Butler in Antigone’s Demand.
Keywords: Antigone family; norm; performativity